2014
DOI: 10.1016/j.applthermaleng.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface functionalities on ethanol adsorption characteristics in activated carbons for adsorption heat pumps

Abstract: To develop high-performance activated carbons (ACs) for adsorption heat pumps (AHPs), it is important to characterize the adsorption behaviors of the refrigerant molecules in the pores of ACs. Not only pore structures, such as pore size and shape, but also surface functionalities strongly influences the adsorption behaviors, especially for polar molecules, such as water and ethanol, which are typical refrigerants for AHP. In this study, we examined the influence of surface functional groups on the adsorption b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Plot of ln(P) vs 1/T at different uptake range for parent Maxsorb III/ethanol pair. Tables Table 1 Elemental composition of adsorbents [23]. Table 2 Composition of ethanol used in experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Plot of ln(P) vs 1/T at different uptake range for parent Maxsorb III/ethanol pair. Tables Table 1 Elemental composition of adsorbents [23]. Table 2 Composition of ethanol used in experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorbents used in the present study are; (i) Parent Maxsorb III which is a highly porous activated carbon powder provided by Kansai Coke & Chemicals Co. Ltd., Japan (ii) a surface treated Maxsorb III (KOH-H2 Maxsorb III), and (iii) H2-surafce treated Maxsorb III. The treatment procedure has been described in reference [20]. Thermo-physical properties and elemental composition of assorted adsorbents are given in Table 1 and 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Temporal histories of adsorption uptake and pressure of Maxsorb III/ethanol pair at adsorption temperature 30ºC. Table 1 Thermo-physical properties of parent and surface treated Maxsorb III [20]. Table 2 Elemental composition of parent, KOH-H2 and H2 treated Maxsorb III [20].…”
Section: Measurement Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Kil et al 16 concluded that abundant surface functionalities decreased the adsorption of ethanol shortened the apparent adsorption equilibrium time. The solid-state NMR and electrochemical analyses conrmed that di®usional hindrance of ethanol molecules caused by surface functionalities in micropores of ACs decreases the adsorption amount and shortens the adsorption equilibrium time of ethanol.…”
Section: Activated Carbon-ethanolmentioning
confidence: 99%